2016
DOI: 10.1080/13543776.2016.1203419
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of EGCG: a patent review

Abstract: Under the current scenario, the role of EGCG as a therapeutic agent is being utilised and new approaches are being formulated to overcome the problem of stability and bioavailability of EGCG. EGCG and its derivatives could be used for the development of drugs for the treatment of cancer, as well as various microbial, metabolic, and neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
141
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(147 citation statements)
references
References 49 publications
(52 reference statements)
0
141
0
1
Order By: Relevance
“…It has been shown to attenuate the inflammatory response (33). The mechanisms of EGCG upon inflammation have been explored in detail.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to attenuate the inflammatory response (33). The mechanisms of EGCG upon inflammation have been explored in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, human studies using these green tea–derived compounds have not been as successful as in vitro and animal studies . There are issues of stability and bioavailability of EGCG, which undergoes metabolism to GA in the gut, so it is unclear if the beneficial metabolic effects of EGCG are due to EGCG or GA . The effects of GA and EGCG on metabolism and PCa are controversial, with some studies showing a benefit and others reporting no effects .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, canonical Notch signaling is important in directing macrophage function in wound repair and would be a potential target for the treatment of nonhealing diabetic wounds (4). In our previous study, (2)-epigallocatechin gallate (EGCG), which is the most abundant catechin in tea (17), was found to attenuate the inflammatory response by shutting off Notch signaling. Further study showed that EGCG could inhibit the LPS-induced inflammation and turn off Notch signaling in human primary macrophages (18).…”
mentioning
confidence: 99%